1993
DOI: 10.1136/jmg.30.3.224
|View full text |Cite
|
Sign up to set email alerts
|

Identification of markers flanking the tuberous sclerosis locus on chromosome 9 (TSC1).

Abstract: Analysis of a large tuberous sclerosis pedigree confirmed linkage to a locus on the long arm of chromosome 9, with recombination events placing the disease gene distal to gelsolin and proximal to dopamine fJ-hydroxylase. (J Med Genet 1993;30:224-7) Linkage analysis in tuberous sclerosis (TSC) is complicated by locus heterogeneity,'2 making it difficult to distinguish recombination from non-linkage and to identify appropriate flanking markers. The problem is exacerbated by the paucity of large affected pedig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 15 publications
(1 reference statement)
1
10
0
Order By: Relevance
“…Initial definition of the 1.5-Mb TSC1 candidate region on chromosome 9q34 was achieved by identification of key meiotic recombination events in large TSC1 families (Haines et al 1991;Nellist et al 1993). Many microsatellite markers from this region were then identified and a cosmid, P1 artificial chromosome and bacterial artificial chromosome contig assembled Povey et al 1994;Van Slegtenhorst et al 1995;Au et al 1996;Hornigold et al 1997).…”
Section: Mapping and Identification Of Tsc1mentioning
confidence: 99%
“…Initial definition of the 1.5-Mb TSC1 candidate region on chromosome 9q34 was achieved by identification of key meiotic recombination events in large TSC1 families (Haines et al 1991;Nellist et al 1993). Many microsatellite markers from this region were then identified and a cosmid, P1 artificial chromosome and bacterial artificial chromosome contig assembled Povey et al 1994;Van Slegtenhorst et al 1995;Au et al 1996;Hornigold et al 1997).…”
Section: Mapping and Identification Of Tsc1mentioning
confidence: 99%
“…Renal cysts are not only seen in patients with TSC2 but also in those with TSC1 mutations [35,36]. Jones et al [6] found unilateral solitary cysts in 3 (of 22) adult patients with TSC1 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that 25% to 61% of affected individuals meet the diagnostic criteria for autism, with an even higher proportion showing features of a broader pervasive developmental disorder [2]. A recent study reported self-injurious behaviour in 10% of people with tuberous sclerosis [3].…”
Section: Introductionmentioning
confidence: 99%